Kualitas air pada pembesaran udang Vaname (Litopenaeus vannamei) PL 8 PT. Budi Agri Sejahtera, Kecamatan Tempilang, Provinsi Bangka Belitung - Ristamaria Manullang; Suzanne L. Undap; Henneke Pangkey; Diane J. Kusen; Ockstan J. Kalesaran; Sammy N.J. Longdong (Universitas Sam Ratulangi, 2023)
This study aims to analyze the parameters of water quality in Post larva (PL) 8 Vanamei shrimp (L. vannamei) by testing physical parameters (temperature, salinity, brightness) and chemical parameters (DO (dissolved oxygen), pH, alkalinity, and hardness. Research conducted at PT. Budi Agri Sejahtera (BAS), Tempilang District, West Bangka Regency, Bangka Belitung Province while conducted Program Kampus Merdeka Magang and Studi Independen Bersertifikat (MSIB). The method uses purposive sampling by setting 5 (five) observation points. Primary data in the form of in situ measurements of water quality parameters obtained in the field. While the analysis of chemical parameters were carried out in the laboratory of PT. BAS in the pond location. Secondary data was carried out by the information of company and journals related to this research. The results of this study indicate that temperature (25-30,2°C), brightness (20-40 cm), salinity (24-31 ppt), DO (3,7-6,3 ppm), pH (7,5-9), Alkalinity (102-150 ppm), Hardness (3,700-5,900 ppm). It was concluded that base on of SNI 01-7246-2006 and Ministry marine and fisheries No: KEP. 28/MEN/2004 the condition of the waters at PT. BAS is still suitable for PL 8 Vanamei shrimp (L. vannamei) cultivate. Keyword: Vaname Shrimp, Water Quality, PT. Budi Agri Sejahtera (BAS), Aquaculture